Brand engagement in self-concept: a comparative study in Austria, Italy and Poland. Issue 7 (10th August 2020) - Razmus, Wiktor; Mazzoli, Valentina; Acuti, Diletta; Grabner-Kräuter, Sonja
Abstract : Purpose: The study aims to shed light on cross-country comparisons of brand engagement in self-concept (BESC) among consumers from European countries and to link presumed differences with country-level economic growth and materialism. This study contributes to the literature on the customer–brand relationship and provides implications for international branding strategies. Design/methodology/approach: This observation study explored levels of BESC in three European countries. Questionnaire data were collected from consumers of Austria ( N = 302), Italy ( N = 431) and Poland ( N = 410) with the purpose to make cross-country comparisons of BESC among consumers. Findings: The results provide evidence for partial scalar invariance of the BESC scale. Cross-country comparisons of latent means reveal that Polish consumers score higher on BESC than consumers from Austria and Italy. Moreover, Austrian consumers score higher on BESC than Italian consumers. Research limitations/implications: Culture as a contextual factor of BESC should be studied further. The findings should be replicated with non-convenience samples in additional cultural contexts to improve the generalizability of data. Structural equation modeling could be used to investigate psychological drivers of BESC differences. Practical implications: The findings coming from the cross-country comparisons of BESC are of practical relevance to marketing managers: they should tailor their branding and communication strategies accordingly. Originality/value: So far, the understanding of cross-cultural and cross-country differences in consumer–brand relationships has remained limited. This study adopts a rigorous approach to cross-cultural research enriching the literature on BESC from a cross-country perspective.